Early prediction of tumor response to carbon ion radiotherapy via 18F-FMISO PET/CT in patients with locally advanced non-small-cell lung cancer - Ren, Caiyue; Chen, Jian; Mao, Jingfang; Zhang, Jiangang; Li, Zili; Wu, Kailiang; Cheng, Jingyi (Frontiers in Oncology, 2025)
BackgroundHypoxia increases resistance to carbon ion radiotherapy (CIRT) in locally advanced non-small-cell lung cancer (LA-NSCLC, stage II-III). This study aimed to develop a hypoxia-related model based on 18F-fluoromisonidazole (FMISO) positron emission tomography/computed tomography (PET/CT) for the early prediction of tumor response to CIRT in LA-NSCLC patients, thereby identifying patients most likely to benefit from CIRT.MethodsA total of 42 LA-NSCLC patients, including 25 (60%) with squamous cell carcinoma (SCC) and 17 (40%) with non-SCC, underwent 18F-FMISO PET/CT prior to CIRT. 18F-FMISO maximum standardized uptake values (SUVmax), the tumor-to-muscle ratios (TMR), and hypoxic tumor volume (HTV) were measured, with the TMR ≥ 1.4 threshold defined for hypoxia. The study endpoint was tumor response to CIRT at 3 months. After identifying 18F-FMISO biomarkers related to CIRT response, a prediction model was developed and evaluated using the area under curve (AUC) (95% confidence interval [CI]).ResultsAmong the 42 patients analyzed, 17 (40%) achieved partial response (PR) while 25 (60%) had stable disease (SD). 18F-FMISO-PET detected obvious uptake in 31 (74%) patients with LA-NSCLC, although these values were not related to CIRT response (p > 0.05). Subgroup analysis showed that favorable responses were significantly more prevalent in hypoxic SCC (TMR ≥ 1.4, n = 15, 36%) patients with smaller HTV (p < 0.01), whereas 18F-FMISO uptake was not significantly correlated with CIRT response in normoxic SCC (TMR < 1.4, n = 10, 24%) or all non-SCC (n = 17, 40%) patients (all p > 0.05). A positive correlation between tumor size and hypoxia was observed in SCC patients (p < 0.01). Multivariate logistic regression analysis showed that HTV was an independent predictor of CIRT response (p = 0.04, odds ratio = 1.14) with an AUC (95% CI) of 0.89 (0.71-1.00) in hypoxic SCC patients.Conclusion18F-FMISO PET/CT is recommended for SCC patients, especially who are likely to have hypoxia predicted by tumor size, and it holds great promise for selecting patients who will benefit from CIRT.